ANALYSIS OF THE BASIC PARAMETERS DESCRIBING THE CONDITION OF IMMUNE SYSTEM IN STOMACH CANCER PATIENTS ASSOCIATED WITH HELICOBACTER PYLORI AND HERPESVIRUSES - Bilyaevskaya, S.Yu.; Cherniavsky, V.I.; Smelianskaya, M.V.; Martynov, A.V.; Peremot, S.D.; Davydova, S.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The condition of immune system at patients with a stomach cancer (SC) was studied. System immunological infringements caused by bacterial-virus associations are revealed. In the greater measure it concerns group of patients with SC and presence НР and HHV in a tumour and in leukocytes. Such infringements are inherent in this group: considerably increased immune-rehulation index, a level of the circulation immune complex, authentic decrease of CD16, index of reaction of a blasttransformation of leucocytes.